Immune Dysregulation and the Pathogenesis of Autism - Lu, MD, PhD, Ping; Kong, MD, Xuejun (North American Journal of Medicine and Science, 2016)
Autism spectrum disorder (ASD) is a devastating disease affecting 1 in 68 children in the United States. Although much has been learned, the etiology and pathogenesis of autism remain largely elusive. More recently, mutations or variants of genes encoding proteins involved in immune regulation have been frequently found in ASD patients, implicating a key role of immune dysregulation in the pathogenesis of ASD. In support of this notion, parental, especially maternal, immune disorders are also identified to be associated with ASD. Further, altered immune responses are constantly observed in ASD patients. On the other hand, restoration of a normal immune system in ASD patients and in animal models has shown promising therapeutic effects, further linking ASD to an abnormal immune state. Here we review current literatures and discuss the potential role of immune dysregulation in driving the pathogenesis of autism. [N A J Med Sci. 2016;9(4):161-166. DOI: 10.7156/najms.2016.0904161] Key Words: immune dysregulation, pathogenesis, autism